In-House Radio-Labelling Of 131i-Rituximab In Threatment Of Cd20+ B-Cell Non-Hodgkin’s Lymphoma: A Pioneer Experience In Malaysia - Kuan, Jew Win; Law, Chiong Soon; Wong, Xiang Qi; Ko, Ching Tiong; Awang, Zool Hilmi; Chew, Lee Ping; Chang, Kian Meng (2016)
Background Radioimmunotherapy (RIT) is an established treatment modality in Non-Hodgkin’s lymphoma (NHL). The only two commercially available RITs - 90Y-ibritumomab tiuxetan (Zevalin®) is expensive and 131I-tositumomab has been discontinued from commercial production. In resource limited environment, 90Y-ibritumomab tiuxetan and autologous haematopoietic stem cell transplantation (HSCT) might not be possible. Self-labelling 131I-rituximab might be the only viable practical option. There is no randomized controlled trial comparing RIT versus autologous HSCT in NHL to examine the possibility of RIT substituting autologous HSCT. We reported our pioneer experience in Malaysia on self-labelling 131I-rituximab, substituting autologous HSCT and a patient, whom to our knowledge, is the first reported case received high dose 131I-rituximab (6000 MBq or 163 mCi) combined with BEAM conditioning for autologous HSCT. Clinical Presentation Six patients (Diffuse Large B-cell Lymphoma (DLBCL) (n = 4), Follicular Lymphoma (FL) grade 2 (n = 2)), who were primary refractory/progressive except one and indicated but unable to receive autologous HSCT, and one primary refractory and progressive Primary Mediastinal (thymic) Large B-cell Lymphoma (PMBL), median age 60 (range 26-62), M:F = 6;1, received self-labelling 131I-rituximab from August to October 2014. Six patients received the usual dosage and one patient with PMBL received high dose combined with BEAM conditioning autologous HSCT. Median follow-up was 15.5 months (range 12.5-16.5). They achieved complete response (CR) (except PMBL - partial response (PR)) as the best response. At the latest follow-up, all the DLBCL remained in CR, one FL had slow progressive disease not symptomatic nor requiring intervention, one FL died after three months of 131I-rituximab due to rectal papillary mucinous adenocarcinoma which was symptomatic and diagnosed after 131I-rituximab, and the PMBL remained in PR. In our very limited experience young patients age less than 60 tolerated the treatment well without grade 4 neutropaenia or thrombocytopaenia. Three out of four elderly patients age 60 or above developed grade 4 haematoloigcal toxicity, which might be related to undiagnosed bone marrow infiltration because two of them had FL. Except for the patient who had developed rectal carcinoma and pre-existing myelodysplastic syndrome (MDS), none developed febrile neutropaenia or required antibiotics. None developed hypothyroidism, myelodysplastic syndrome or acute myeloid leukaemia, albeit follow-up is still short. Intervention (& Technique) The usual dosage: 5 mCi on Day 0 (dosimetry dose) and total-body dose 0.75 Gy on Day 7 (therapeutic dose). High dose: 6000 MBq (163 mCi) on Day -18 combined with BEAM conditioning, started on Day -8, for autologous HSCT. Discussion/Conclusion Self-labelled 131I-rituximab may be a viable option to substitute autologous HSCT in refractory/relapse NHL, especially when autologous HSCT is not feasible. It is is definitely cheaper and halves the cost of Zevalin®. Its use in PMBL warrants further study.